Medial patellar ligament reconstruction in combination with derotational distal femoral osteotomy for treating recurrent patellar dislocation in the presence of increased femoral anteversion: a systematic review - Jinghong Yang; Jun Zhong; Han Li; Yimin Du; Xu Liu; Zhong Li; Yanshi Liu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Medial patellar ligament reconstruction (MPFL-R) in combination with derotational distal femoral osteotomy (DDFO) for treating recurrent patellar dislocation (RPD) in the presence of increased femoral anteversion is one of the most commonly used surgical techniques in the current clinical practice. However, there are limited studies on the clinical outcomes of MPFL-R in combination with DDFO to treat RPD in the presence of increased femoral anteversion. Purpose To study the role of MPFL-R in combination with DDFO in the treatment of RPD in the presence of increased femoral anteversion. Methods A systematic review was performed according to the PRISMA guidelines by searching the Medline, Embase, Web of Science, and Cochrane Library databases through June 1, 2023. Studies of patients who received MPFL-R in combination with DDFO after presenting with RPD and increased femoral anteversion were included. Methodological quality was assessed using the MINORS (Methodological Index for Nonrandomized Studies) score. Each study’s basic characteristics, including characteristic information, radiological parameters, surgical techniques, patient-reported outcomes, and complications, were recorded and analyzed. Results A total of 6 studies with 231 patients (236 knees) were included. Sample sizes ranged from 12 to 162 patients, and the majority of the patients were female (range, 67-100%). The mean age and follow-up ranges were 18 to 24 years and 16 to 49 months, respectively. The mean femoral anteversion decreased significantly from 34° preoperatively to 12° postoperatively. In studies reporting preoperative and postoperative outcomes, significant improvements were found in the Lysholm score, Kujala score, International Knee Documentation Committee score, and visual analog scale for pain. Postoperative complications were reported in all studies, with an overall reported complication rate of 4.7%, but no redislocations occurred during the follow-up period. Conclusion For RPD with increased femoral anteversion, MPFL-R in combination with DDFO leads to a good clinical outcome and a low redislocation rate. However, there was no consensus among researchers on the indications for MPFL-R combined with DDFO in the treatment of RPD.